High robust eddy current tuned tandem mass dampers-inerters for structures under the ground acceleration - Cao, Liyuan; Li, Xueqin; Huang, Yu; Li, Chunxiang; Pan, Hang (Soil dynamics and earthquake engineering (1984), 2025)
In this work, a novel eddy current tuned tandem mass dampers-inerters, referred to as EC-TTMDI is proposed, a theoretical analysis model of the vibration control mechanism is established, and parameterized analysis and design are conducted using the intelligent optimization algorithm. This model is the single-degree-of-freedom (SDOF) structure with EC-TTMDI subjected to Gaussian white noise base excitation. Specifically, the expression for the displacement variance of the SDOF structure-EC-TTMDI system was firstly obtained with resorting to both the equivalent linearization of eddy current damper (ECD) and residue theorem. The optimization objective function was then defined as minimization of the displacement variance, which is product of the white noise intensity and the square of H2 norm of the model transfer function. Employing the pattern-search algorithm, the variation trends of the objective function and the optimum design parameters were subsequently scrutinized. The vibration damping mechanism of EC-TTMDI is then revealed in terms of control effectiveness, robustness, structural frequency response, suppression bandwidth, and stroke. Finally, the time history response analysis of the SDOF structure-EC-TTMDI system subjected to the near-field impulse, near-field non-impulse, and far-field earthquakes was conducted to further confirm the performance superiority of EC-TTMDI. Results demonstrates that EC-TTMDI offers higher robustness and better control effectiveness compared to TTMDI and TMDI. Furthermore, EC-TTMDI features the damping force limiting characteristic, which enhances the integrity and reliability of TTMDI. •Novel eddy current-based tuned tandem mass dampers-inerters (EC-TTMDI) is proposed.•Optimum EC-TTMDI is acquired via pattern search to minimize displacement variance.•EC-TTMDI remarkably enhances bandwidth and robustness compared with TMDI and TTMDI.•EC-TTMDI has better displacement control effectiveness compared to TMDI and TTMDI.•Self-limiting ECD forces of EC-TTMDI lifts the integrity and reliability of TTMDI.